Al-ghazali kimiya-e saadat: the alchemy of happiness - Field, Claude (Islamic Book Trust Kuala Lumpur, 2007)
Al-Ghazali Kimiya-e Saadat: The Alchemy of Happiness presents a philosophical exploration of inner contentment and spiritual fulfillment, drawing on the teachings of Al-Ghazali to guide readers towards a meaningful life.